Volume 6B: Turbomachinery 2013
DOI: 10.1115/gt2013-94656
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis of a Boundary-Layer-Ingesting Distortion-Tolerant Fan

Abstract: The paper describes the aerodynamic CFD analysis that was conducted to address the integration of an embedded-engine (EE) inlet with the fan stage. A highly airframe-integrated, distortion-tolerant propulsion preliminary design study was carried out to quantify fuel burn benefits associated with boundary layer ingestion (BLI) for “N+2” blended wing body (BWB) concepts. The study indicated that low-loss inlets and high-performance, distortion-tolerant turbomachines are key technologies required to achieve a 3–5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Flow field measurements and simulations have shown that distortion leads to a large-scale flow redistribution upstream of a compressor rotor, leading to non-uniform velocity and swirl angles at its leading edge, [20][21][22][23][24]. In many of these studies the rotor is found to operate at high incidence in localised regions of the annulus, with a flow coefficient below the critical clean-flow value, while the machine as a whole remains stable.…”
Section: Introductionmentioning
confidence: 99%
“…Flow field measurements and simulations have shown that distortion leads to a large-scale flow redistribution upstream of a compressor rotor, leading to non-uniform velocity and swirl angles at its leading edge, [20][21][22][23][24]. In many of these studies the rotor is found to operate at high incidence in localised regions of the annulus, with a flow coefficient below the critical clean-flow value, while the machine as a whole remains stable.…”
Section: Introductionmentioning
confidence: 99%
“…To reap the benefits of BLI, a stronger distortion tolerant fan design with blades designed to straighten out the swirl flow is required [74]. UTRC and NASA Glenn Research Centre (GRC) made collaborative efforts in designing a fan aiming to limit the efficiency deterioration within 1-3% [85]; Figure 3 displays the wind tunnel test for a distortion tolerant propulsor fan to observe the impact from varying wind speeds on the operability, structure, and performance of the fan.…”
Section: Boundary Layer Ingested Electric Propulsion System Design-bementioning
confidence: 99%
“…In regions of reduced mass flux and higher incidence, the Mach number will be reduced and this could help reduce the stator losses behind the distorted region. Such effects are visible in [1,2,4] and this suggests the amount of non-axisymmetric design variation required in a transonic fan may be lower than for a low speed case. circumference at midspan, the maximum wake thickness occurs within -60° < θ < 30°.…”
Section: Turbo-18-1356mentioning
confidence: 99%
“…Similar features have been observed in highspeed fans and compressors operating with inlet total pressure distortion. For example, in [2] full unsteady calculations were performed of a coupled inlet and transonic fan operating with BLI. The fan pressure ratio was 1.35 and the inlet distortion had a similar form to that used in the current study.…”
Section: Introductionmentioning
confidence: 99%